The investigation of fuzzy logic-PI based load frequency control of Keban HEPP - Taşar, Beyda; Güler, Hasan; Özdemir, Mehmet (Control Engineering and Applied Informatics Journal, 2015)
The Keban Hydroelectric Power Plant (HEPP) consists of eight synchronous generators, all of which are interconnected to the power system. In this study, we examine the frequency changes and stability of the Plant with respect to a possible load change in the power system. It is important to keep the frequency constant while the power systems are fulfilling the requested power. Thus, in order to keep the system frequency stable in the event of a possible change in power request, a Fuzzy-logic based proportional-integral (FPI) controller, which can maintain its stability even in the event of system parameter changes, is proposed in this study. The design of this system was performed in Matlab/Simulink Software, and the performance results were compared with the results achieved through a traditional proportional-integral (PI) controller. To simulate the system, we constructed a model of the Keban Hydroelectric Power Plant based on the catalog values.
Keywords: Frequency stability; Fuzzy logic controller; Keban Hydroelectric Power Plant; Proportional integration control hydroelectric power plant